Biotransformation of disperse dyes using nitroreductase immobilized on magnetic particles modified with tosyl group: Identification of products by LC-MS-MS and theoretical studies conducted with DNA - Franco, Jefferson Honorio [UNESP]; da Silva, Bianca F. [UNESP]; de Castro, Alexandre A.; Ramalho, Teodorico C.; Pividori, María Isabel; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2018)
The present work evaluates the action of nitroreductase enzyme immobilized on Tosylactivated magnetic particles (MP-Tosyl) on three disperse dyes which contain nitro and azo groups. The dyes included Disperse Red 73 (DR 73), Disperse Red 78 (DR 78), and Disperse Red 167 (DR 167). The use of a magnet enabled the rapid and easy removal of the immobilized enzyme after biotransformation; this facilitated the identification of the products generated using high-performance liquid chromatography with diode array detector (HPLC-DAD) and mass spectrometry (LC-MS/MS). The main products formed by the in vitro biotransformation were identified as the product of nitro group reduction to the correspondent amine groups, which were denoted as follows: 50% of 2-(2-(4-((2-cyanoethyl)(ethyl)amino)phenyl)hydrazinyl)-5-nitrobenzonitrile, 98% of 3-((4-((4-amino-2-chlorophenyl) diazenyl)phenyl) (ethyl)amino)propanenitrile and 99% of (3-acetamido-4 - ((4-amino-2-chlorophenyl) diazenyl) phenyl) azanediyl) bis (ethane-2,1-diyl) for DR 73, DR 78 and DR 167, respectively. Based on the docking studies, the dyes investigated were found to be biotransformed by nitroreductase enzyme due to their favorable interaction with the active site of the enzyme. Theoretical results show that DR73 dye exhibits a relatively lower rate of degradation; this is attributed to the cyanide substituent which affects the electron density of the azo group. The docking studies also indicate that all the dyes presented significant reactivity towards DNA. However, Disperse Red 73 was found to exhibit a substantially higher reactivity compared to the other dyes; this implies that the dye possesses a relatively higher mutagenic power. The docking results also show that DR 73, DR 78 and DR 167 may be harmful to both humans and the environment, since the mutagenicity of nitro compounds is associated with the products formed during the reduction of nitro groups. These products can interact with biomolecules, including DNA, causing toxic and mutagenic effects. To sum up, the results point out that both the original textile dyes and their degradation products may pose serious risks to human health and the environment at large.
Keywords: Biotransformation; Disperse dyes degradation; Enzyme immobilized onto magnetite; Nitroreductase